Atomic force microscopy study of nanoporous gold surface and electrochemical properties. (15th July 2019) - Gao, Panpan; Qian, Ping; Qiao, Lijie; Volinsky, Alex A.; Su, Yanjing
Abstract: The morphology, surface oxide and strain evolution of nanoporous (np) gold were investigated using atomic force microscopy (AFM). Topographic AFM images show typical np structure with a few nanometers ligament size. Current sensing AFM results revealed semiconductor properties of the surface oxide, which may consist of Ag2 O (p-type) and AgO (n-type). The surface oxide can effectively suppress the np structure coarsening. In-situ electrochemical AFM tests exhibit a refined macroscopic dimensional change of 40 nm within 0.35–0.7 V potential range. AFM can be used as an effective method to investigate the morphology and voltage-induced dimension changes in electrolyte. Graphical abstract: AFM topography images of (a) the initial prepared npg and (b) the reduced npg samples.Unlabelled Image